Strategies for Development of Yoga, Ayurveda, and Meditation-based Health Tourism in Nepal: Using SWOT Analysis (Journal of Tourism & Adventure, 2019)
Now health tourism based on yoga, Ayurveda and meditation is growing sector in Nepalese Tourism. Health tourism as one of the most important forms of tourism is not an exception and preparing strategies for its development will not be possible without considering its specific and extraordinary environment. The objective of preparing and is writing this research paper is to formulate suitable strategies for health tourism development in Nepal. This study uses a qualitative approach. We conduct 38 semi structured interviews with related stakeholder’s of health tourism in Nepal, including health service providers, tourism service providers (as enterprise), and government officials. It was carried out in 2017 in Kathmandu, Bhaktapur, Lalitpur, and Pokhara. For strategy formulation, we employ the Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis method to examine the internal and external factors comprehensively, in terms of health tourism development in Nepal. The strategy to the health tourism development will be considered in terms of four relations: strengths-opportunities (S-O), weaknesses-opportunities (W-O), strengths-threats (S-T), weakness-threats (W-T). The results of this study show that the strategy in health tourism development in Nepal, it is necessary to work on policy and regulation, promotion and branding, introducing the quality standards for health products and service as well as to establish the institutional support in order to successful implementation for the strategy of the health tourism development in Nepal.